2020
DOI: 10.1371/journal.pone.0228389
|View full text |Cite
|
Sign up to set email alerts
|

Motor activation is modulated by visual experience during cyclic gait observation: A transcranial magnetic stimulation study

Abstract: Transcranial magnetic stimulation (TMS) has been widely utilized to noninvasively explore the motor system during the observation of human movement. However, few studies have characterized motor cortex activity during periodic gait observation. Thus, this study examined the effects of an observer's visual experience and/or intention to imitate on corticospinal excitability during the observation of another's gait. Twenty-six healthy volunteers were included in this study and allocated to two different groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Our first finding of MEP amplitude increasing while participants watched another person’s action including an object and goal is consistent with previous TMS studies [ 23 25 ]. One study showed that corticospinal excitability increased in recordings from the tibialis anterior and soleus muscles during gait observation [ 26 ]. Another study found MEP facilitation during observations of direct movement [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our first finding of MEP amplitude increasing while participants watched another person’s action including an object and goal is consistent with previous TMS studies [ 23 25 ]. One study showed that corticospinal excitability increased in recordings from the tibialis anterior and soleus muscles during gait observation [ 26 ]. Another study found MEP facilitation during observations of direct movement [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen healthy volunteers (sex, seven men and seven women) aged 20–22 years (mean age, 20.6 ± 0.6 years) without history of neurological or psychiatric disorders participated in the study. As our previous research had explored the effect of visual experience on motor cortical activity during gait observation [ 26 ], the participants who had formal experience with gait observation in clinical education were excluded from this study. Prior to conducting the experiments, we confirmed that all participants were right-handed using the Edinburgh Handedness Inventory [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Motor-evoked potentials (MEPs) induced by TMS during action observation are reported to be closely coupled to the muscles involved in the action execution [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and the temporal pattern of the observed action [ 14 , 15 , 22 , 23 , 24 ], which are remarkable and meaningful findings elucidated by TMS studies. Regarding the motor system activity during mere cyclic gait observation, prior TMS studies have demonstrated that the motor resonance to the observed whole-body gait movement was enhanced in the crural flexor and extensor muscles throughout the step cycle [ 25 , 26 ], which is incompatible with the kinematic feature of actual walking in terms of the time course of muscle activity. Although AOT is often used to improve walking ability in clinical settings [ 4 , 7 , 9 ], the motor cortical activity while observing human bipedal walking is not well-known; for example, it is unknown whether this curious motor resonance during gait observation replicates the original time course of the motor cortical activity during gait execution, or whether it is interfered with by factors affecting the inner automatic motor response process of the observed gait in a top-down modulation manner [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that different imagery perspectives are mediated through separate neural systems, which contribute differently during processes of motor learning and neurological rehabilitation ( Mulder, 2007 ). Besides, previous experience or gaining experience by observing repetitive movements may facilitate motor learning of the specific task ( Ito et al, 2020 ). However, the discrepancies between the different types and perspectives of cognitive practice, as well as the control of the subjects’ actual involvement in the practice, could be overcome by modifying and adapting old strategies such as PME with MVF to the rehabilitation practice of patients with orthopedic lower limb disorders, or by using a new tool such as the VR practice.…”
Section: Future Perspectives and Recommendations For Improvement Of C...mentioning
confidence: 99%